Czy pytać to tylko ‘zadawać pytanie’? Kilka uwag o medialnym użyciu tego czasownika - Ciunovič, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*74.66px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00363);" role="presentation">The verb <span dir="ltr" style="left: calc(var(–scale-factor)*113.11px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967221);" role="presentation">pytać <span dir="ltr" style="left: calc(var(–scale-factor)*136.56px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01161);" role="presentation">[to <span dir="ltr" style="left: calc(var(–scale-factor)*150.31px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992766);" role="presentation">ask] is one of the basic <span dir="ltr" style="left: calc(var(–scale-factor)*243.53px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985596);" role="presentation">verba dicendi<span dir="ltr" style="left: calc(var(–scale-factor)*296.90px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00092);" role="presentation">, thus its meaning seems obvi<span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*132.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01187);" role="presentation">ous and its lexicographical descriptions exhaustive. At the same time, contemporary <span dir="ltr" style="left: calc(var(–scale-factor)*75.24px); top: calc(var(–scale-factor)*146.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01665);" role="presentation">uses of this lexeme in the media suggest the presence of additional components, not <span dir="ltr" style="left: calc(var(–scale-factor)*74.91px); top: calc(var(–scale-factor)*160.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03784);" role="presentation">yet taken into <span dir="ltr" style="left: calc(var(–scale-factor)*134.45px); top: calc(var(–scale-factor)*160.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03186);" role="presentation">account in the studies of this verb. The author will therefore analyse <span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01426);" role="presentation">selected quotations from informative Internet portals and <span dir="ltr" style="left: calc(var(–scale-factor)*308.86px); top: calc(var(–scale-factor)*175.55px); font-size: calc(var(–scale-factor)*8.60px); font-family: serif; transform: scaleX(1.06637);" role="presentation">TV <span dir="ltr" style="left: calc(var(–scale-factor)*323.78px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01238);" role="presentation">dailies in order to <span dir="ltr" style="left: calc(var(–scale-factor)*397.46px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05052);" role="presentation">then <span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999394);" role="presentation">attempt to <span dir="ltr" style="left: calc(var(–scale-factor)*117.41px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988923);" role="presentation">answer the question <span dir="ltr" style="left: calc(var(–scale-factor)*197.77px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985231);" role="presentation">posed in the title. The description <span dir="ltr" style="left: calc(var(–scale-factor)*331.49px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.964679);" role="presentation">will take into <span dir="ltr" style="left: calc(var(–scale-factor)*384.22px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01368);" role="presentation">account <span dir="ltr" style="left: calc(var(–scale-factor)*75.21px); top: calc(var(–scale-factor)*202.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.994071);" role="presentation">the pragmatic elements of the utterance: its context, information <span dir="ltr" style="left: calc(var(–scale-factor)*332.02px); top: calc(var(–scale-factor)*202.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01134);" role="presentation">about the sender and <span dir="ltr" style="left: calc(var(–scale-factor)*75.21px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00144);" role="presentation">the assumed recipient, as well as the entire communication <span dir="ltr" style="left: calc(var(–scale-factor)*313.09px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.006);" role="presentation">situation; the conclusions <span dir="ltr" style="left: calc(var(–scale-factor)*74.93px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0094);" role="presentation">will, in turn, be confronted with descriptions of the verb <span dir="ltr" style="left: calc(var(–scale-factor)*303.73px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967221);" role="presentation">pytać <span dir="ltr" style="left: calc(var(–scale-factor)*327.19px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0117);" role="presentation">[to <span dir="ltr" style="left: calc(var(–scale-factor)*340.94px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0182);" role="presentation">ask] present in the <span dir="ltr" style="left: calc(var(–scale-factor)*75.17px); top: calc(var(–scale-factor)*244.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.987999);" role="presentation">linguistic literature.